2020
DOI: 10.3389/fpsyg.2020.00614
|View full text |Cite
|
Sign up to set email alerts
|

Is Dispositional Self-Compassion Associated With Psychophysiological Flexibility Beyond Mindfulness? An Exploratory Pilot Study

Abstract: Background: Dispositional mindfulness and self-compassion are shown to associate with less self-reported emotional distress. However, previous studies have indicated that dispositional self-compassion may be an even more important buffer against such distress than dispositional mindfulness. To our knowledge, no study has yet disentangled the relationship between dispositional self-compassion and mindfulness and level of psychophysiological flexibility as measured with vagally mediated heart rate variability (v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 81 publications
0
3
0
Order By: Relevance
“…Recent studies (Svendsen et al, 2016(Svendsen et al, , 2020Luo et al, 2018) and meta-analytic evidence (Di Bello et al, 2020) showed that both state (i.e., induced) and trait (i.e., dispositional) compassion, toward oneself and others, are related to higher vmHRV (Di Bello et al, 2020). Additionally, compassion-focused practices can improve vmHRV (Rockliff et al, 2008;Arch et al, 2014;Matos et al, 2017;Petrocchi et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies (Svendsen et al, 2016(Svendsen et al, , 2020Luo et al, 2018) and meta-analytic evidence (Di Bello et al, 2020) showed that both state (i.e., induced) and trait (i.e., dispositional) compassion, toward oneself and others, are related to higher vmHRV (Di Bello et al, 2020). Additionally, compassion-focused practices can improve vmHRV (Rockliff et al, 2008;Arch et al, 2014;Matos et al, 2017;Petrocchi et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…However, previous research has also suggested that dispositional SC, rather than dispositional mindfulness, may be an even more effective buffer against emotional distress. In fact, preliminary results from a pilot study indicated that dispositional SC is a stronger predictor of vagally-mediated heart rate variability (vmHRV) than mindfulness (Svendsen et al, 2020 ). Accordingly, the findings are in line with recent trends in the clinical mindfulness field (Feldman and Kuyken, 2011 ; Segal et al, 2018 ; Conversano et al, 2020 ), which point to a greater explicit focus on SC in mindfulness-based interventions and support clinical work targeting SC (Conversano et al, 2020 ).…”
mentioning
confidence: 99%
“…As a state of kindness towards self, it might emerge from mindful attention and awareness as a result of an individual being attentive toward its inner feelings and thoughts of suffering [27] . Self-compassion was therefore recognized, along with measures of distress, as a significant correlate [28,29,30] and an important convergent measure [13,31] of Mindful attention and awareness, and its conceptually similar constructs [32] .…”
Section: Discussionmentioning
confidence: 99%